Character Building Through Muhadharah Activities in Islamic Junior High Education: Pembentukan Karakter Melalui Kegiatan Muhadharah dalam Pendidikan Menengah Islam - Aji, Hendi Prasetyo; Astutik, Anita Puji (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Character education plays a pivotal role in shaping students' behavior and mindset, especially in Islamic educational settings. Specific Background: At SMP Muhammadiyah 6 Pucuk Lamongan, concerns have arisen regarding students’ declining discipline, politeness, and moral conduct. Knowledge Gap: Despite numerous studies on character education, limited research addresses the role of muhadharah (religious speech practice) in systematically forming character in junior high school students within Islamic institutions. Aim: This study aims to investigate the implementation of muhadharah activities and analyze the character values cultivated through these practices. Methods and Results: Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving teachers, students, and administrators. The findings indicate that character development through muhadharah follows three stages: insight, engineering, and adaptation. The activities significantly foster bravery, politeness, discipline, cooperation, responsibility, literacy, and broad insight among students. Novelty: This research uniquely highlights muhadharah as an effective Islamic extracurricular framework for character formation, combining religious values with structured developmental stages. Implications: The findings suggest that muhadharah can serve as a replicable model for Islamic character education in other institutions facing similar behavioral challenges. Highlights : Highlights muhadharah as a tool for character development. Uses a structured three-stage formation model. Addresses behavioral issues in Islamic junior high schools Keywords: Character, Muhadharah, Islamic Education, Student Behavior, Extracurricular